Uso de processos oxidativos avançados para fotodegradação de componentes do petróleo em águas de alta salinidade - Freitas, Deivyson Roris de (2012)
The purpose of this study was to verify the efficiency of the removal and degradation of oil and grease present inthe saline oily water, using the heterogeneous photocatalysis (Fe3O4/H2O2/UV) with artificial white light batch reactor using pure magnetite and magnetite doped cobalt. A factorial design 23was made where the parameters considered were the lamp power, peroxide concentration, and the time of exposure to UV radiation. An interesting proposal in this study was to make a photocatalytic reactor using an artificial source of UV radiation, which is a mercury vapor lamp of high pressure, arranged so that the effluent receives as many photons as possible. For the experiments were used synthetic solutions that simulate the produced water with varying concentrations of oils and greases. The colorimetric method was used to determine the oil and grease contents (O&G). The samples from the oxidative experiment were extracted and measured in the spectrophotometer at 256 nm. The effects of hydrogen peroxide, the influence of the composition of magnetite in the process of O&G removal, and the turbidity of the samples were evaluated. The addition of hydrogen peroxide with a concentration of 500mg/L, showed an increased removal of O&G by 80% using the 125W lamp power and 94% degradation using the 250W lamp power. The photo-Fenton degradation tests for synthetic water production were conducted by varying only the type of catalyst and the dosage of hydrogenperoxide while maintaining the pH at 3.0 and the lamp power at 125 W. The process showed to be very efficient by getting removal indices of 93% using magnetite cobalt. All experiments achieved satisfactory results in the degradation of oil compoundsandtheremoval of the turbidity by photolysis and photo-Fenton reaction.